2019
DOI: 10.1590/1983-21252019v32n204rc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Competition and Water Deficiency on Sunflower and Weed Growth

Abstract: In the agricultural environment, the occurrence of biotic and abiotic stresses, such as weed interference and soil water deficit is common. However, little is known about the effects of the interaction of these stresses on the growth of cultivated crops and weed species. Thus, the objective of this study was to evaluate the effects of competition and water deficiency on the growth of sunflowers and weeds. The experiment was performed in a randomized block design with four replications. The treatments were arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Easy dispersion and high seed production capacity allow both B. pilosa and B. subalternans to colonize cultivated and noncultivated areas (PAMPLONA et al, 2020). In addition, these species have a great capacity to extract water and nutrients from the soil, making these species good competitors for growth resources, during various crop cycles (SANTOS et al, 2015;FREITAS et al, 2019;SOARES et al, 2019). According to Deiss et al (2017), losses of productivity in the range of 30% in the soybean crop occurred due to the interference of B. pilosa and B. subalternans.…”
Section: Introductionmentioning
confidence: 99%
“…Easy dispersion and high seed production capacity allow both B. pilosa and B. subalternans to colonize cultivated and noncultivated areas (PAMPLONA et al, 2020). In addition, these species have a great capacity to extract water and nutrients from the soil, making these species good competitors for growth resources, during various crop cycles (SANTOS et al, 2015;FREITAS et al, 2019;SOARES et al, 2019). According to Deiss et al (2017), losses of productivity in the range of 30% in the soybean crop occurred due to the interference of B. pilosa and B. subalternans.…”
Section: Introductionmentioning
confidence: 99%
“…The average productivity of sunflower crops in the worldwide was 1803.9 kg/ha in 2019 (FAO, 2019). Many environmental factors contributed to the nonachievement of greater productivity in the sunflower harvest in Brazil, which highlights the increase in the frequency of drought seasons (Soares et al, 2019). Large economic losses were reported for Brazilian agribusiness, primarily due to periods of severe drought in the field (Ribeiro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Bianchi et al (2011) achieved different results from ours, since competition with radish (Raphanus sativus L.) in the vegetative stage of soybean led to a decrease in height, branch length and grain productivity. A study of sunflower plants grown alone and together with slender amaranth (Amaranthus spinosus) showed that the water deficit regime affected the growth rate of the crop and led to shorter plants (Soares et al, 2019).…”
Section: Resultsmentioning
confidence: 99%